حصر الإصابة بفيروس تدهور الحمضيات على أصناف حمضيات مزروعة في محافظة طرطوس، سورية - حمدان, رحاب; مخول, جرجس; إسماعيل, عماد (Latakia University Journal -Biological Sciences Series, 2013)
تم التقصي عن الإصابة بفيروس تدهور الحمضيات (التريستيزا) في 14 بستاناً في مناطق مختلفة في محافظة طرطوس في الساحل السوري خلال ربيع عام 2012، حيث تم خلال عمليات المسح جمع 691 عينة من أصناف مختلفة، تحمل معظمها أعراضاً شبيهة بالأعراض التي تسببها الأمراض الفيروسية (تقزم، اصفرار، موزاييك، تدهور سريع، شفافية العروق، أوراق قميّة على شكل القارب أو الملعقة)، وبعضها لا تحمل أعراض إصابة ظاهرية نظراً لاحتمال وجود إصابات كامنة. فُحصت العينات باستخدام اختبار البصمة النسيجية المناعية (TBIA) وتبين أن نسبة الإصابة بالفيروس في العينات المختبرة بلغت 34.15%، وسُجل وجود الفيروس في جميع مناطق الدراسة بنسب متفاوتة، وبلغت أعلى نسبة في العينات التي جمعت من موقع الحميدية (62.50 %)، بينما كانت أقل نسبة في مشتل تالين الزراعي (10%). وكانت أعلى نسبة إصابة في العينات التي جمعت من صنف البرتقال البلدي ((%41.43، ولم تسجل إصابات في العينات التي جمعت من صنف المندلينا. A survey of infection by Citrus tristeza virus (CTV) was conducted during a visit to 14 citrus orchards in different regions in Tartous governorate in the Syrian Coast during the spring of 2012. We collected a total of /691/ samples of different varieties. Most of the samples were collected from plants with symptoms similar to symptoms caused by viral diseases (dwarfing, yellowing, mosaic, quick- decline, vein clearing, boat or spoon-shaped leaves), while other samples did not carry such symptoms due to the possible presence of latent infections. The samples were tested by using Tissue Blot immunoassay (TBIA). The Results showed that the rate of infection by CTV was 34.15% in the tested samples and the distribution of CTV in citrus orchards was by various ratios. The highest percentage of infection was detected in AL- Hamidiah (62.50%), whereas the lowest infection percentage detected was in Talin nursery (10%). Common orange Balady was the most infected by Citrus tristeza virus (41.43%). No virus infection was recorded in Mandalina samples.